Pengaruh Jumlah Penumpang dan Durasi Buka Tutup Pintu Terhadap Perubahan Suhu (Studi Kasus: Kereta Inspeksi PPI Madiun) - Syafitri, Wasis Desti Cindy; Puspitasari, Mariana Diah; Winjaya, Fathurrozi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The inspection train is specialized equipment used for examining railway tracks, transporting personnel, and carrying work equipment. The inspection train must be equipped with operational tools, monitoring equipment, and work comfort equipment. One of the comfort equipment is air circulation control, which should provide comfort to the personnel while working. Factors influencing the air temperature inside the inspection train include the number of passengers and duration of door opening. This research employs the Design of Experiment data processing method, with the data analyzed using a 2-factor factorial design experiment, with the assistance of Minitab software to understand the influence of the number of passengers and the duration of door opening-closing on temperature changes inside the inspection train. The result obtained from Minitab analysis indicate that the number of passengers has a significant influence on temperature changes inside the inspection train, accounting for 5.2% of the variation. On the other hand, the duration of door opening-closing does not have a significant effect on temperature changes. Additionally, the interaction between the number of passengers and the door open-close duration does not have a significant influence on temperature changes inside the PPI Madiun Inspection Train.